Digital Transformation of Arts Learning for Early Childhood: The Effect of E-Module on Learning Achievement of Early Childhood Education Undergraduate Students - Suci Aprilyati Ruiyat; Uswatun Khasanah; Eneng Sri Susilawati; Otto Fajarianto (JTP - Jurnal Teknologi Pendidikan, 2026)
learning achievement of Early Childhood Education (ECE) undergraduate students in an arts learning course. The research background is rooted in the low digital transformation of arts learning in Indonesian higher education, with 81% of lecturers still relying on conventional teaching materials and student mean scores remaining at 63.8 out of 100. Employing a quantitative approach with a quasi-experimental Pretest-Posttest Control Group Design, this study involved 64 fourth-semester ECE students divided into an experimental group (n=32) using e-modules and a control group (n=32) using printed modules. Data was collected through validated learning outcome tests, student response questionnaires, and observation sheets. The e-module was assessed as highly feasible by content experts (91.6%) and media experts (90.4%). The independent-samples t-test revealed a significant difference in posttest scores: experimental group (M=84.22, SD=7.93) versus control group (M=70.47, SD=9.18), t (62) = 6.74, p<0.001, with Cohen's d=1.67 indicating a very large effect size. These findings confirm that e-module-based digital transformation significantly enhances ECE students' arts learning achievement and supports the advancement of 21st-century pedagogical practice in higher education.